Stress among Police Officers in Singapore : associations with coping responses and subjective wellbeing. - Nisha Lakshmi Ganasekeran. (2010)
This study examined stressors of 274 police officers and associations with coping responses, overall mental health and Asian Subjective Wellbeing (ASWB). Police stressors were identified using in-depth interviews and survey of a representative sample of the Singapore Police Force (N = 10). The main police stressors were Work, Public Expectations, Health, Sleep, Work-Life Integration and Personal stressors. Correlation analyses showed all stressors positively correlated with mental health problems, while only Health, Sleep and Personal stressors were positively correlated with ASWB; all stressors were positively correlated with Problem-Focused, Non-Problem-Focused and Religious-based coping; Problem-Focused coping was positively correlated with ASWB; Non-Problem-Focused coping was negatively correlated with ASWB and positively correlated with mental health problems; Religious-based coping was positively correlated with family ASWB.